1997
DOI: 10.1016/s0092-8674(00)81924-8
|View full text |Cite
|
Sign up to set email alerts
|

LEF-1, a Nuclear Factor Coordinating Signaling Inputs from wingless and decapentaplegic

Abstract: wingless and decapentaplegic signal during endoderm induction in Drosophila to regulate expression of the homeotic gene Ultrabithorax. Here, we define a minimal wingless response sequence in the midgut enhancer of Ultrabithorax. We show that this sequence is recognized by the murine transcription factor LEF-1 (lymphocyte enhancer binding factor 1) in a ternary complex with armadillo protein, the cytoplasmic target of the wingless signaling pathway. In stable transformants, transcriptional stimulation of the Ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
310
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 406 publications
(323 citation statements)
references
References 60 publications
13
310
0
Order By: Relevance
“…The first test of multimerized T-cell factor (TCF) sites in vivo was performed in Drosophila (Riese et al, 1997). Four copies of a TCF binding site, taken from a Wntregulated midgut enhancer of the Ultrabithorax (Ubx) gene, were placed upstream of a minimal TATAcontaining promoter driving lacZ.…”
Section: Transgenic Tcf Reporters: a Brief Historymentioning
confidence: 99%
See 3 more Smart Citations
“…The first test of multimerized T-cell factor (TCF) sites in vivo was performed in Drosophila (Riese et al, 1997). Four copies of a TCF binding site, taken from a Wntregulated midgut enhancer of the Ultrabithorax (Ubx) gene, were placed upstream of a minimal TATAcontaining promoter driving lacZ.…”
Section: Transgenic Tcf Reporters: a Brief Historymentioning
confidence: 99%
“…Four copies of a TCF binding site, taken from a Wntregulated midgut enhancer of the Ultrabithorax (Ubx) gene, were placed upstream of a minimal TATAcontaining promoter driving lacZ. This binding site is necessary for Wnt-mediated activation of the Ubx enhancer in vivo (Riese et al, 1997;Yu et al, 1998). However, transgenic flies carrying the multimerized TCF site reporter construct showed no lacZ expression in Wnt-responding cells, even upon overexpression of the Wingless ligand (Riese et al, 1997).…”
Section: Transgenic Tcf Reporters: a Brief Historymentioning
confidence: 99%
See 2 more Smart Citations
“…This marked the beginning of her interest in the molecular mechanisms of Wnt signal transduction. She pinpointed the Wingless-responsive element within the midgut enhancer from the homeotic gene Ultrabithorax, and demonstrated that TCF/LEF factors acted through this element to mediate the Wingless response (Riese et al, 1997). Soon after this, the critical role of the Wnt signalling pathway in cancer began to emerge.…”
Section: Dr Mariann Bienzmentioning
confidence: 99%